Penguatan Program Kampung Iklim Melalui Edukasi Digital, Pengelolaan Sampah Organik, Dan Ketahanan Pangan Berkelanjutan Di Desa Timbanuh - Imam Fathurrahman; Muhammad Djamaluddin; M. Nurul Wathani; Ida Wahidah (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
Timbanuh Village has considerable potential to support the implementation of the Climate Village Program (ProKlim). However, the community still faces several challenges, including suboptimal household organic waste management, limited utilization of organic waste, and high dependence on chemical pesticides that may negatively affect environmental quality. This community service program aimed to improve community knowledge, skills, and participation in environmental management and food security through digital education and environmentally friendly practices. The program was implemented using a participatory approach involving socialization, mentoring, hands-on activities, and the development of digital educational media that can be accessed sustainably by the community. The activities included socialization on organic waste management, assistance in eco-enzyme production, development of digital educational media, tree planting, and training on the preparation of botanical pesticides. The results demonstrated improvements in community knowledge and skills in managing organic waste, utilizing eco-enzymes, applying botanical pesticides, and increasing access to environmental information through digital media. This program contributed to enhancing community capacity to implement sustainable environmental management practices and supported community-based climate change mitigation and adaptation efforts in Timbanuh Village